2020
DOI: 10.1111/famp.12622
|View full text |Cite
|
Sign up to set email alerts
|

“This is not your Life…and it becomes your Life”: A Qualitative Exploration of Deployment‐related Stress and Support needs in National Guard and Reserve spouses who are Mothers of Young Children

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Qualitative studies indicate that service members and at-home partners identify online communication and social media platforms as both helpful and unhelpful for maintaining relationships during deployment (Blow et al, 2021; Larsen et al, 2015; Messecar, 2017; Rea et al, 2015). Military couples report that technologically mediated communication channels are valuable for facilitating real-time conversation, updating each other on everyday events, sharing pictures, and feeling reassured about the partner’s safety (Bóia et al, 2018; Larsen et al, 2015; Rea et al, 2015), but on the other hand, mediated interaction can be distressing if missed contact sparks worry (Ross et al, 2021), the service member feels helpless to assist with problems at home (Messecar, 2017; Strong & Lee, 2017), or the at-home partner inadvertently witnesses warfighting during a real-time conversation (Larsen et al, 2015; Messecar, 2017). Structural barriers such as unreliable technology or communication outages at the base can hamper communication as well (Blow et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative studies indicate that service members and at-home partners identify online communication and social media platforms as both helpful and unhelpful for maintaining relationships during deployment (Blow et al, 2021; Larsen et al, 2015; Messecar, 2017; Rea et al, 2015). Military couples report that technologically mediated communication channels are valuable for facilitating real-time conversation, updating each other on everyday events, sharing pictures, and feeling reassured about the partner’s safety (Bóia et al, 2018; Larsen et al, 2015; Rea et al, 2015), but on the other hand, mediated interaction can be distressing if missed contact sparks worry (Ross et al, 2021), the service member feels helpless to assist with problems at home (Messecar, 2017; Strong & Lee, 2017), or the at-home partner inadvertently witnesses warfighting during a real-time conversation (Larsen et al, 2015; Messecar, 2017). Structural barriers such as unreliable technology or communication outages at the base can hamper communication as well (Blow et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Protective factors may be critically important to the well-being and mission readiness of military families. 13,27 The hypothesized association between social support and reintegration outcomes was borne out, suggesting that spouses with more social support were likely to report a shorter reintegration phase. Although social support did not exert significant indirect effects through subjective preparedness, a significant total effect on the length of reintegration through subjective preparedness was observed.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,13,18,26 Qualitative work with military spouses suggests that combat stress reactions, in particular, can complicate reintegration processes. 27 Although less studied, spouse mental health may be as -or more -strongly associated with family reintegration challenges. Spouse depression has been associated with their own and their partner's reports of reintegration difficulties.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deployment cycle is associated with a series of transitions and separations that create stress for families. In particular, deployment separation appears to increase military spouse distress (Mansfield et al, 2010), potentially increasing their difficulty meeting children’s developmental needs (Ross et al, 2020), which is hypothesized to increase incidence of child neglect observed during deployment separation (Gibbs et al, 2007). Though the reintegration phase of deployment has been linked to increases in maltreatment as well (Rentz et al, 2007; Taylor et al, 2016), the association of parental trauma exposure, whether combat-related or not, with child maltreatment outcomes has not been adequately explored in this population.…”
Section: Military-specific Factors Associated With Maltreatmentmentioning
confidence: 99%